Upaya Meningkatkan Kepercaya Diri Siswa Melalui Konseling Sebaya (Peer Counseling) di SMA Negeri 9 Bandar Lampung - Triani, Sri Puji (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2017)
By looking at the relationship between the more dynamic teenagers, the BK Teachers can anticipate the provision of BK services by utilizing their peers as a means to be able to provide assistance to their peers. In this PTK researchers improve on efforts to improve student self-confidence. The sample that the researcher took was based on the sociometric assessment data where there were isolated students in the class. The isolated student is assisted by the most favorite students with peer counseling training and it is shown that peer counseling can help improve students' self-confidence.